A study of STP strategies of Chinese retail banking industry for competitive advantage - Wen, Manqing (2006)
This dissertation reports on the research in how Chinese domestic banks use Segmentation, Targeting and Positioning (STP) strategy for retail banking in the context of anticipated competition after 2006 when the banking business will be fully open to foreign banks. With the full liberalization of China's banking sector due under China's WTO commitments, Chinese domestic banks are faced with the need to increase their competitiveness.